THE USE OF THE AUTOMATED DIGITAL ZENITH CAMERA SYSTEM IN ISTANBUL FOR THE DETERMINATION OF ASTROGEODETIC VERTICAL DEFLECTION - Albayrak, Müge; Halıcıoğlu, Kerem; Özlüdemir, Mustafa Tevfik; Başoğlu, Burak; Deniz, Rasim; Tyler, Allison RB; Aref, Mohammed Mohseni (Boletim de Ciências Geodésicas, 2019)
The Digital Zenith Camera Systems (DZCSs) are dedicated astrogeodetic instruments used to obtain highly accurate astrogeodetic vertical deflection (VD) data. The first Turkish DZCS, the Astrogeodetic Camera System (ACSYS), was developed in Istanbul, Turkey in 2015. The ACSYS was capable of determining astrogeodetic VDs with an accuracy of ~0.3 arcseconds. However, it had some limitations in observation duration: because of the semi-automated mechanical design, levelling the system towards zenith was a time-consuming process. Since 2016, the ACSYS has been modernized through system upgrades and new technological components. In this paper, we describe the instrument design of the new DZCS—ACSYS2—observation procedures, evaluation of the test data and calculations of these data. The preliminary ACSYS2 astrogeodetic test observations were conducted at Istanbul Technical University (ITU) test station. The standard deviation results of the repeated observations reveal a VD measurement precision of ~0.3 arcseconds for both the North-South and East-West components. To investigate the accuracy of the system, a lightweight total station based-geodetic system—QDaedalus—was also used at the ITU test station. The comparison of the VDs data between ACSYS2 and QDaedalus system shows that the ACSYS2 can produce reliable VDs data.